Sistema supervisório de unidades de microgeração de energia elétrica: o caso da geração de eletricidade com o biogás - Otto, Rodrigo Bueno (2015)
The generating units form a distributed power generator system that uses biogas as fuel, this biogas is produced on small farms that collect the waste from agricultural activities systems. The supervisory system of the biogas generation units can monitor local and remote environmental, electrical and mechanical variables of the process and display this data in a user-friendly interface for analysis and decision making. In addition to providing an user interface, the data collected will be stored to build the process history and analysis database that will serve as a study source and promotion of new research lines related to this topic.